A Modified Genetic Algorithm in C++ for Optimization of Steel Truss Structures - Pawan Kumar; Shivam Pandey; Pabitra Maiti (Journal of soft computing in civil engineering, 2021)
A common structural design optimization problem is weight minimization which is done by choosing a set of variables that represent the structural or the architectural conﬁguration of the system satisfying few design specific criterion. In general, genetic algorithms (GAs) are ideal to be used for unconstrained optimization, so it is required to transform the constrained problem into an unconstrained one. A violation of normalized constraints-based formulation method has been used in the present work for this purpose. A modified algorithm has been developed in C++ using concept of genotypes for optimization using discreet design variable. A detailed analysis of optimization of a simple steel truss with discrete design variables using different variations of genetic algorithm is presented here. Also, an attempt has been made to study the sensitivity of the algorithm with respect to the optimization operators i.e., initial population size, rate of mutation.